TAXATION OF HOLDING COMPANIES IN THE NETHERLANDS: A SOUTH AFRICAN OBSERVATION - Thabo Legwaila (Obiter, 2021)
The South African government has expressed an intention to market itself as a gateway to investment in Africa. This will be achieved inter alia by redesigning certain aspects of the tax laws in order to encourage investment into South Africa in the form of headquarter companies as a special kind of holding companies. The Netherlands has over time adjusted its tax regime to achieve the same goal, viz, to attract holding companies for investment into European countries and globally. Specifically, the Dutch participation exemption and the advance-tax ruling system have been hailed as the key tax instruments that are instrumental in attracting foreign residents to set up holding companies in the Netherlands. Furthermore, the intentional absence of various tax instruments such as controlled foreign-company provisions and exchange-control regulations further enhance the Netherlands’ suitability to host holding companies. In light of the South African government’s intentions to attract holding companies, it is important to study the Dutch system applicable to holding companies to see what attributes, if any, South Africa could also adopt.